ASSESSMENT OF LONGITUDINAL VARIATION OF TROPHIC LEVELS OF THE RED RIVER WATER, THE SECTION FROM HANOI CITY TO BA LAT ESTUARY - Binh, Phung Thi Xuan; Da, Le Nhu; Quynh, Le Thi Phuong; Ha, Hoang Thi Thu; Thuy, Duong Thi; Hanh, Le Thi My (Vietnam Journal of Marine Science and Technology, 2019)
The Red river system is a typical example of Southeast Asian rivers that is strongly impacted by human and climatic conditions, especially in the recent period. In this paper, we aim to investigate the longitudinal variation of the water quality of the Red river, in the section from Hanoi city to the Ba Lat estuary. The sampling campaigns were conducted in the dry seasons in 2017 and 2018. The monitoring results showed that the average concentrations of nutrients (NO2-, NO3-, NH4+, PO43-) were still lower than the allowed values of the Vietnamese standard limits for surface water quality (QCVN 08:2015/BTNMT, column A1) whereas the average concentrations of Cl- and TSS exceeded the allowed values of the QCVN 08:2015/BTNMT, column A1 4.6 and 2.3 times, respectively. NO3- and dissolved silica (DSi) concentrations showed a significant variation from the Hanoi site to the Ba Lat site (6.62 mg/l to 1.19 mg/l for NO3- and 5.21 mg/l to 2.14 mg/l for DSi) whereas SO42-, NO2- and Cl- increased markedly in this longitudinal section, especially from the point SH6 where the salinity started to increase. Based on the three different methods for classification of trophic levels and on the different variables observed during the dry seasons in 2017–2018, the nutrient concentrations of the Red river water tended to slightly increase from the site Hanoi (SH1) to the site SH5 at Nam Dinh, indicating the increase of nutrient external input along the river whereas it tended to decrease from the site SH6 (at mesotrophic/eutrophic level) to the last observed site SH9 (at oligotrophic/mesotrophic level) at the sea due to the dilution of seawater. Seawater in dry season could affect directly the river downstream about 35 km far from the sea. The results may be a guide for planning of water use including agricultural irrigation in the Red river estuary.